2013
DOI: 10.4028/www.scientific.net/ssp.208.70
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Supporting Structures of HV Lines Using Magneto-Mechanical Effects

Abstract: This paper concerns the idea of using magneto-mechanical effects in prophylactic activities to reduce the risk of occurrence of an extensive blackout on high voltage (HV) lines. The subject matter of the paper is related to the event from April 8, 2008, which deprived approximately 600,000 recipients from 18 cities of the West Pomeranian voivodeship of power and caused millions in losses for the national economy. In theoretical considerations, the idea of diagnosing the technical state and level of effort of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In order to control the surface layer of ferromagnetic materials and the quality of the laser treatment, is proposed an implicit relationship that exists between the chemical composition of the material, its structure, mechanical, and physical parameters. On the basis of the literature [4][5][6][7][8][9][10][11][12] was found that the magnetic and electrical parameters of the material are very sensitive diagnostic indicators, which is used in non-destructive magnetic tests. For initial research and atypical exploration of research problems (assessment of microstructure and stress in industrial conditions), three research methods were used:…”
Section: Selection Of Non-destructive Testing Methodsmentioning
confidence: 99%
“…In order to control the surface layer of ferromagnetic materials and the quality of the laser treatment, is proposed an implicit relationship that exists between the chemical composition of the material, its structure, mechanical, and physical parameters. On the basis of the literature [4][5][6][7][8][9][10][11][12] was found that the magnetic and electrical parameters of the material are very sensitive diagnostic indicators, which is used in non-destructive magnetic tests. For initial research and atypical exploration of research problems (assessment of microstructure and stress in industrial conditions), three research methods were used:…”
Section: Selection Of Non-destructive Testing Methodsmentioning
confidence: 99%
“…There are also magnetic anomalies (M A i q. A reliable interpretation of test results of MMM is connected with obtaining additional information about DUT geometric, distance of magneto-meters from DUT and potential sources of artificial magnetization of DUT material [13]. Quantitative analysis of test results of MMM is controversial due to the lack of reliable data on:…”
Section: Examplesmentioning
confidence: 99%
“…It was noted that changes of the quality of own magnetic field of a ferromagnetic object can occur due to geometrical non-continuity, while quantitative changes will be the outcome of changes of a ferromagnetic material's volume and its magnetic properties (Iwaniec et al, 2014). These phenomena emerge under the influence of the Earth's magnetic field and can be associated with an object's magnetic state (magnetization of an object), which form certain image (a signature) of the magnetic field belonging to a given moving object.…”
Section: Physical Conditionsmentioning
confidence: 99%